HUBUNGAN PEMBERIAN REWARD DENGAN MINAT BELAJAR SISWA DI SEKOLAH MTs DARUL ILMI KELAS VIII TAHUN AJARAN 2021/2022 - Rahmarani Akmal Hia; Eryanti Lisma (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the relationship between reward and interest in learning in class VIII MTs Darul Ilmi Batang Kuis. Based on the results of observations, it is known that during the learning process the teacher has given rewards but not optimally. This is rarely done because the teacher thinks that when students get good grades, it makes students happy. In fact, students also want their work to be recognized and appreciated so that they are more motivated to increase their interest in learning. The formulation of the problem in this study is